Towards spacecraft applications of structural health monitoring - Adrian TOADER; Victor GIURGIUTIU; Ioan URSU (INCAS Bulletin, 2012)
The first part of the paper presents recent developments in the field of structural health monitoring (SHM) with special attention on the piezoelectric wafer active sensors (PWAS) technologies utilizing guided waves (GW) as propagating waves (pitch-catch, pulse-echo), standing wave (electromechanical impedance), and phased arrays. The second part of the paper describes the challenges of extending the PWAS GW SHM approach to in-space applications. Three major issues are identified, (a) cryogenic temperatures; (b) high temperatures; and (c) space radiation exposure. Preliminary results in which these three issues were address in a series of carefully conducted experiments are presented and discussed. The third part of the paper discusses a new project that is about to start in collaboration between three Romanian institutes to address the issues and challenging of developing space SHM technologies based on PWAS concepts. The paper finishes with conclusions and suggestions for further work.